The reflections produced by lumped load of digital signal line - Golumbeanu, Virgil; Svasta, Paul; Ionescu, Ciprian (Видавництво Національного університету "Львівська політехніка", 2002)
In interconnection technique of digital circuits in general the matched lines method for reducing the influence of reflections in a view to a good working of interconnected circuits is used. Due to the input capacitance of digital circuits appears a reactance load. Although the matching is very good realized from the viewpoint of the resistive load, there is a reactive mismatching that can produce reflections at high frequency. Using Laplace transformation the reflections produced by parasitic capacitance load will be determined. These reflections will be analyzed depending on the type of the digital circuits and the parameters of the interconnection line. For some types of digital circuits the maximum fanout from this point of view will be determined.
Keywords: printed circuit board; reflections; digital circuits; capacitance load